ON ADMISSION TO THE CLERGY: VOCATION AND FAMILY STRATEGIES IN EIGHTEENTH CENTURY SPAIN - Irigoyen López, Antonio (Revista de Historia Social y de las Mentalidades, 2017)
This paper aims to reflect on the reasons why people decided to become clerics. For this we will resort to the analysis of various works of ecclesiastical treatises written in Spain during the eighteenth century. It is verified that joining the Church was not a free and personally decision taken by those involved, but other reasons were considered, in particular family strategies: someone entered the Church to favor his family. Faced with this situation, ecclesiastical texts advocated that people should only enter the Church with true vocation, otherwise, would never be good ecclesiastical ministers. This reality was very common in Eighteenth Century Spain, which should be corrected through written plays for the priests became aware of the importance of their mission